Improving Students’ Speaking Ability Trough Students Teams Achievement Devision ( STAD ) at The Second Grae Students of SMA Katolik Delimurni Delitua - Marice Saragih; Dippu Pasaribu; Jaya Perkas (Journal of Classroom Action Research, 2022)
The objectives of this research are find out the students ability in speaking through Students Team Achievement Devision (STAD) at the second grade SMU Katolik Delitua . The good teacher is able to find the good strategy in the teaching and learning process so that the students will interest to study English. One of strategy used in teaching speaking ability is Students Team Achievement Devision (STAD) . The population of this study was all of the second grade of SMU Delimurni which consist of 60 students. The sample consist of this research are 30 students. This study use quantitative research using an experimental design and control design, the examiner intentionally revised appearance of the difference and then it was examined how the result was. This research required two groups of student namely experimental group and control group. experimental group was treated with Students Team Achievement Devision (STAD) during studying English . where as control group was treated without Students Team Achievement Devision (STAD) it can be seen that the mean score of the pre-test in the control group is 46.35 and the post-test 57.30, and mean of deviation is 10,95. it means that the deviation is low. From the total score pre test of the experimental class (1.600) and the total score pre test of the control class (1.360) can be concluded that the achievement of both group was the same. After getting the treatment Students Team Achievement Devision (STAD) , the total score post-test of the experimental (2.337) was higher than the total score post-test of the control class (1.686) which did not get the treatment. It can be said that Students Team Achievement Devision (STAD Strategy can improve the students ability in speaking and this strategy provide the students’ Motivation and enthusiasms in learning English. Key Words : Speaking, Students Team Achievement Devision ( STAD)